PECULIARITIES OF UNIVERSITY PARTNERSHIP NETWORKS PRESENTATIONS - Semen E. Il'in; Ekaterina V. Filatova (Высшее образование в России)
The article tests out the criteria for comparing data on activity of partnership networks of higher education institutions presented on their websites. The authors give a comparative analysis of self-presentations provided by the three world's top universities - Massachusetts Institute of Technology, Cambridge University and Imperial College London. Considerable attention is focused on peculiarities of presentation of network partners, interactions with and between partners, and also prospects for development of partnership networks. The proposed criteria have proved effective in identifying common features and differences in the way higher education institutions supply information about their partnership networks.